Physiological response of 5/1 intermittent aerobic exercise and its relationship to 5 km endurance performance - Babineau, C.; Leger, L. (International Journal of Sports Medicine, 1997)
A great number of specialists and coaches believe that conventional laboratory measurements lack specificity and that more practical testing should be instituted. The majority of studies have addressed this issue by looking at the relationship between physiological variables and time trials (TT). However, few have examined the pertinence of standardized aerobic interval training (AIT) programs to a simulated race performance or time trial. We studied 23 athletes (runners and multi-sport) to determine if their performance on the track during regular strenuous intermittent workouts would be associated with the 5000 m TT. The 3 interval track workouts each totalling 4800 m with a work to rest ratio of about 5 to 1, consisted of either 12 x 400 m (15 s rest), 6 x 800 m (30 s rest) or 3 x 1600 m (60 s rest) and performed at maximal cruising speed (maxCS). Correlation coefficients between the 400, 800, 1600 m workouts and 5000 m TT were not significantly higher (0.90, 0.95, 0.93) than those for VO2max (0.84) or maximal aerobic speed (0.85). When considering only the work interval, the mean %HRmax for the AIT and TT were accomplished respectively at 97.5 and 97.3 for the runners and 95.9 and 95.7 for the multi-sport athletes. In conclusion, our results indicate that the AIT programs performed with brief rest periods during normal training periods are as capable of predicting 5000 m race performance as are laboratory measurements. Also, within the limit of this study, the 6 x 800 m (30 s rest) AIT workout seems to be a very efficient and specific manner to simulate a competitive endurance performance.